Old vs. New Money in The Great Gatsby (2013) and Indonesian Culture: A Marxist Film Analysis - Nazwa Maisya Nasution; Alifah Hasti Nayla; May Debora Lovefian Br. Manurung; Raden Roro Diandra Putri Amanda (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The representation of wealth and how it is inherited often determines a person's position in the social structure. The difference between old wealth and new wealth reflects different lifestyles, values, and forms of social recognition. This study aims to analyze Baz Luhrmann’s 2013 film adaptation of The Great Gatsby, how the film depicts class and social inequality, and reflect on its relevance to contemporary Indonesian society. Using a descriptive qualitative approach, the analysis focuses on cinematic elements such as setting, characters, and visual symbols that represent the contrast between “old money” and “new money.” Guided by Marxist theory, this study explores how the film depicts class struggle, capitalism, and the illusion of social mobility. The results of the study reveal two key findings. First, the film affirms that new wealth does not automatically confer cultural legitimacy, as the social structure remains controlled by established groups. Second, this representation is relevant to the Indonesian context, where differences in lifestyle, access, and privilege between “old money” and “new money” are still strongly visible in urban social life. However, this study has limitations because it only examines one film and does not use empirical data from Indonesian society. Overall, The Great Gatsby criticizes capitalist inequality and illustrates how class divisions persist over time, both in 1920s America and in Indonesia today.